A constitutive model for a rate and temperature-dependent, plastically anisotropic titanium alloy. (November 2020) - Ruiz de Sotto, Miguel; Longère, Patrice; Doquet, Véronique; Papasidero, Jessica
Abstract: Aircraft engine fan blades are notably designed to withstand impact loading involving large deformation, high strain rate, non-proportional loading paths and self-heating. Due to their high strength-to-weight ratio and good toughness, Ti–6Al–4V titanium alloys are promising candidates for the blades leading edge. An extensive experimental campaign on a Ti–6Al–4V titanium alloy provided in the form of cold rolled plates has been carried out. The thermo-mechanical characterization consisted in tension, compression and shear tests performed at various strain rates and temperatures, and under monotonic as well as alternate loading paths. A constitutive model has been accordingly developed accounting for the combined effect of plastic orthotropy and tension/compression asymmetry, nonlinear isotropic and kinematic strain hardening, strain rate hardening, and thermal softening. The constitutive model has been implemented as a user material subroutine into the commercial finite element computation code LS-DYNA. The performances of the model have been estimated by conducting numerical simulations considering a volume element under various loading paths as well as the specimens used for the experimental campaign. Highlights: The effect of orientation, strain rate, temperature and loading path on a Ti–6Al–4V titanium alloy response is investigated. Plastic anisotropy, isotropic hardening, strain rate hardening and thermal softening are accounted for in an advanced model. Anisotropic effects include plastic orthotropy, tension-compression asymmetry and nonlinear kinematic hardening . The performances of the numerical version (user material subroutine) of the model are evaluated using LS-DYNA .